2017
DOI: 10.1038/s41598-017-10601-w
|View full text |Cite
|
Sign up to set email alerts
|

TRIB3 inhibits proliferation and promotes osteogenesis in hBMSCs by regulating the ERK1/2 signaling pathway

Abstract: Osteogenic differentiation in human bone marrow-derived mesenchymal stem cells (hBMSCs) is regulated by various factors, including bone morphogenetic proteins (BMPs), Notch, growth hormones and mitogen-activated protein kinases (MAPKs). Tribbles homolog 3 (TRIB3), a pseudokinase, plays an important role in cancer cells and adipocytes. However, TRIB3 function in osteogenic differentiation is unknown, although it is involved in regulating signaling pathways associated with osteogenic differentiation. Here, we fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…IGF-1 is a type of growth factor that plays an important role in regulating the proliferation, differentiation and apoptosis of tissue cells ( 17 ). Previous studies have also reported that IGF-1 could regulate the proliferation, differentiation and apoptosis of BMSCs through the STAT3/Akt, ERK1/2, BMP2, PI3K/AKT signaling pathways ( 18 , 19 ). However, there are few reports on the role of Wnt/β-catenin pathway in these processes.…”
Section: Discussionmentioning
confidence: 94%
“…IGF-1 is a type of growth factor that plays an important role in regulating the proliferation, differentiation and apoptosis of tissue cells ( 17 ). Previous studies have also reported that IGF-1 could regulate the proliferation, differentiation and apoptosis of BMSCs through the STAT3/Akt, ERK1/2, BMP2, PI3K/AKT signaling pathways ( 18 , 19 ). However, there are few reports on the role of Wnt/β-catenin pathway in these processes.…”
Section: Discussionmentioning
confidence: 94%
“…p38 MAPK is closely associated with apoptosis and cell cycle changes in many malignant tumors. In in human bone marrow-derived mesenchymal stem cells (hBMSCs), TRIB3, regulated by FAK in a way that depends on PI3K/AKT, played an vital role in proliferation and osteogenic differentiation by modulating ERK1/2 activity at the middle stage of differentiation [ 29 ]. In renal cell carcinoma (RCC), researchers have found that high expression of TRIB3, which is induced by HIF-1α, enhanced cell proliferation, migration and invasion abilities by regulating the MAPK pathway [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of MAPKs in osteogenesis is contradictory. A recent study has demonstrated that TRIB3 influenced proliferation and differentiation in the middle stage of differentiation by inhibiting the ERK1/2 [ 44 ]. As mentioned above, the molecular mechanism that TLR4 is involved in controlling the fate of MSCs toward osteogenesis is still uncovered.…”
Section: Discussionmentioning
confidence: 99%